A new Borhyaenoid (Mammalia, Metatheria, Sparassodonta) from the middle Eocene of Salta Province, Argentina - Babot, Judith (2010)
We describe a new borhyaenoid found at the upper levels of the Lumbrera Formation (Casamayoran SALMA, Barrancan subage) exposed at the locality of El Simbolar, southern Salta Province, Argentina. The material is represented by partially preserved cranial and postcranial remains. The upper molars present a basined lingual portion of the trigon, and a conspicuous protocone. The paraconule and metaconule are present. The stylar shelf bears the parastyle, the stylocone and the cusp C, being the stylocone the most developed element. The most striking feature of the lower molars is the presence of a vestigial metaconid located posterolingually to the protoconid. The talonid is basined and presents a well developed hypoconulid, vertically directed, and very small entoconid and hypoconid. The dentition in this specimen is similar in size to that of Borhyaenidium Pascual and Bocchino and Sipalocyon Ameghino. Nevertheless, the presence of significative differences with these and other borhyaenoids (e.g., presence of metaconid, small but basined talonid, presence of entoconid, hypoconid, and hypoconulid) allows us to refer this material to a new taxon. A phylogenetic analysis including most of the sparassodonts known by well preserved specimens, showed this specimen as a basal form. This material represents the first sparassodont found at the upper levels of the Lumbrera Formation. Other records (e.g., Patene Simpson, Callistoe Babot, Powell and Muizon), come from lower levels, recently referred to the Vacan subage of the Casamayoran.